Student Investor’s Attentiveness In Islamic Stocks - Ana Fitria; Teuku Syifa Fadrizha Nanda; Dhea Purnama Nurman (Jurnal Investasi Islam, 2021)
The stock market is a meeting place for investors and go public companies, one of parties included in investors is student of faculty of economics and business that is expected to become an expert in the stock market. Student investor’s attentiveness is influenced by several factors such as the return perception and financial literacy. This study employs a quantitative associative approach while a set of questionnaire were asked to students of Faculty of Islamic Economics and Business, UIN Ar-Raniry Banda Aceh. Using multiple linear regression analysis, it showed that both return perception and financial literacy affect investment attentiveness. However, both independent variables only contribute 29% to affect dependent variable; there are other variables affect the investment attentiveness which were not included in this study. Either adding more variables or using different type of research method is suggested for further study.